59th National conference of anatomical society of India - Khan, Aaijaz Ahmed (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2011)
Aim ofthe study: To evaluate the acceptability of peer teaching in osteology Materials and method: 60 students of 1" year MBBS 2010-11 batch at StJohn's Medical College were included in the study. They were divided into six groups of 10 students and were given specific objectives as handouts for each osteology class. Initially, for upper limb osteology sessions, three groups had active learning with peer teaching and the other three had didactic lectures by tutors. These groups were interchanged for lower limb osteology. Following this all6 groups were involved in active peer teaching for the rest of osteology. A questionnaire based on Ukhert scale was used to determine student response to peer teaching technique. Results: 83.3% of the students agreed that peer teaching had improved their understanding of osteology. 90% of the students recommend the continuation of the peer teaching methodology for osteology in the following years. 70% of the students recommended the peer teaching method for embryology and histology. The students found the hand outs very comprehensive and helpful. They f~t that it helped them revise osteology quickly before exams. Further details will be dealt during presention. Conclusion: Our study showed that medical undergraduates are able to successfully participate in a structured teaching program and derive a unique perspective to exam preparation that was very well received by our student cohort. The role of students teaching their own peers in a formal structured environment is a very valuable teaching tool and the researchers feel this should be encouraged.